Script of the commentary on the touch screen video clips on some rock art and cave art sites in Tamilnadu - Kannan, R. (Chennai The COmmissioner of Museums, 2002)
The Rock and Cave Art Gallery is a unique effort to simulate reality and present it in a Museum Gallery. It commemorates the completion of 150 years of the founding of the Government Museum, Chennai (Madras).
Keywords: IAS as an author; Art